The main aspects of the reasons and a consequence of political crises in some socialist countries in 50 years of the XX century (International relations and international law Journal, 2018)
In countries of Eastern Europe in which the model of a state system of the totalitarian type construct- ed on the Soviet sample constantly was already in the late forties approved arose, socio-political and economic crises developed and went deep. Deterioration in a level of living of the population against the background of violation of democratic freedoms was a consequence of copying of the Soviet experience     of social and economic transformations. As the argument confirming such conclusions it is possible to     read out powerful social and political crises in Poland, Hungary and GDR 1953-1956, on the one hand,      and sharp strengthening of repressive policy of the state for any dissent, from another. Studying of history of the Hungarian events of 1956 is of particular importance for all post-socialist countries as it I was the    first open armed protest against the Soviet dictatorship. The crucial role of a power factor in preservation   of Eastern Europe under control of the USSR has been visually shown to the whole world. The Hungarian events have ingenerated also a crisis situation of the world communistic movement as in a number of       the Communist Parties split between those who, acting under a banner of «national communism», have condemned, and those who have supported the Soviet actions in Hungary was outlined. Besides strong-  arm tactics of the USSR has pushed away to the west from the communistic movement of many of those who sympathized with him earlier, first of all intellectuals.Key words: Hungary, GDR, Poland, command system, state, policy, crisis.